Pengembangan Aplikasi Forum Komunitas Sepeda berbasis Web - Elvin Nikolas; Nurudin Santoso (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Currently, the trend of cycling still draws quite a lot of interest among Indonesian society. This causes many bicycle communities are scattered in various regions of Indonesia. Usually, every community has an online community group as a medium for its members to interact with each other and exchange information. However, the use of social media as the main medium for the bicycle community has its deficiency because it's still scattered across different social media platforms such as Facebook, Kaskus and WhatsApp. In addition, there is also difficulty for new people to find a community that suits their preferences because the lack of information about the existing communities. With these deficiencies, a bicycle community forum application is developed to address the existing deficiencies and hopefully can meet the needs of the Indonesian bicycle community. The Rapid Application Development method is chosen as the development method in this research in order to accelerate the development process and deliver product according to its needs. The main system development technologies used in this research are React.js, Node.js, MongoDB and GraphQL. For system testing, black box and white box are used as the testing techniques. The results of the two tests generate correct and valid outputs, indicating that all functional requirements of the system have been met and the system are running as it is expected.